Brigatinib for ALK-positive metastatic non-small-cell lung cancer: design, development and place in therapy - Ali R; Arshad J; Palacio S; Mudad R (Dove Medical Press, 2019)
Robert Ali,1 Junaid Arshad,1 Sofia Palacio,1 Raja Mudad2 1Department of Medicine, Division of Oncology, Jackson Memorial Hospital, University of Miami, Miller School of Medicine, Sylvester Comprehensive Cancer Centre, Miami, FL 33131, USA; 2Department of Medicine, Division of Oncology, University of Miami, Miller School of Medicine, Sylvester Comprehensive Cancer Centre, Miami, FL 33136, USA Abstract: Despite the benefits of first and second generation anaplastic lymphoma kinase (ALK) inhibitors in the management of ALK-rearranged advanced non-small-cell lung cancer (NSCLC), the development of acquired resistance poses an ongoing dilemma. Brigatinib has demonstrated a wider spectrum of preclinical activity against crizotinib-resistant ALK mutant advanced NSCLC. The current review narrates a brief history of tyrosine kinases, the development and clinical background of brigatinib (including its pharmacology and molecular structure) and its use in ALK-positive NSCLC. Keywords: non-small cell lung cancer, ALK positive, ALK inhibitors, brigatinib, TKI